2010
DOI: 10.1186/2047-783x-15-6-238
|View full text |Cite
|
Sign up to set email alerts
|

Home-based subcutaneous immunoglobulin G replacement therapy under real-life conditions in children and adults with antibody deficiency

Abstract: Background Subcutaneous immunoglobulin (SCIG) therapy is an alternative to intravenous immunoglobulin (IVIG) therapy. Methods We evaluated the efficacy and safety of the SCIG Vivaglobin ® (formerly known as Beriglobin ® SC) under real-life conditions in a post-marketing observational study in 82 patients with primary or secondary antibody deficiencies. Health-related quality of life (HRQoL) was evaluated in a subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 30 publications
6
37
0
2
Order By: Relevance
“…However, the frequency of infections reported overall was similar between patients receiving either treatment. This finding is compatible with previous studies that showed that IVIG and SCIG are equally effective in protecting against infections [21][22][23][24][25]. However, patients on IVIG reported higher infection rates towards the end of the infusion cycle, which was associated with the wear-off effect of IgGRT [26,27], and patients who switched from IVIG to SCIG reported less wear-off effect and less fatigue [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…However, the frequency of infections reported overall was similar between patients receiving either treatment. This finding is compatible with previous studies that showed that IVIG and SCIG are equally effective in protecting against infections [21][22][23][24][25]. However, patients on IVIG reported higher infection rates towards the end of the infusion cycle, which was associated with the wear-off effect of IgGRT [26,27], and patients who switched from IVIG to SCIG reported less wear-off effect and less fatigue [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, AUC is not a clinically established marker for evaluating Ig pharmacokinetics, and trough values may be more appropriate (13). Our clinic employs a general 1:1 dose conversion ratio when switching patients from IVIG to SCIG, and our findings corroborate other studies that have reported 1:1 dose conversion to be an appropriate strategy when switching patients from IVIG to SCIG (5,(14)(15)(16)(17). In this cohort of pediatric patients, monthly SCIG dosing was actually lower, on average, than prior IVIG dosing.…”
Section: Discussionsupporting
confidence: 77%
“…The usual practice of switching from IVIG to SCIG therapy in Europe has been to use the equivalent monthly IgG dose split into four equal weekly doses (1:1 dosing) [68,69]. Despite the recommendation of the US Food and Drug Administration to use a dose adjustment coefficient to achieve similar total exposure to IgG (non-inferior area under the curve of serum IgG concentration plotted versus time) [16], studies of clinical practice in the United States suggest that physicians are not necessarily heeding that recommendation, as there was no difference in the total monthly doses used by the intravenous and subcutaneous routes [70,71].…”
Section: Dose Intervalsmentioning
confidence: 99%
“…SCIG administration has been reported to be more compatible with an active lifestyle, including sports and schooling, and more convenient during business trips or holiday [13,21,24,[26][27][28]68,69]. Ninety per cent of patients receiving IVIG report having skipped a dose compared with 18% of those receiving SCIG therapy, and 45% of patients with SCIG self-administered doses with delay by 3 or more days at least once in the last 6 months [8,13].…”
Section: Special Situationsmentioning
confidence: 99%